(untitled) (Journal of Mathematical Study, 2022)
Our aim in this paper is to study a coupled Cahn–Hilliard system for copolymer/homopolymer mixtures. We prove the existence, uniqueness and regularity of solutions. We then prove the existence of finite dimensional global attractors.